Bail-out extracorporeal membrane oxygenation for hydroxychloroquine intoxication: a warning for COVID-19 health-care givers. Issue 2 (4th March 2021) - Holvoet, Wouter; van Soest, Kaja; Havenith, Thomas; Lorusso, Roberto; van Mook, Walther N. K. A.; Delnoij, Thijs
Abstract: This case report describes an intentional intoxication with 18 g of hydroxychloroquine (HCQ) presenting with unconsciousness, ventricular dysrhythmias, cardiogenic shock and pulmonary oedema. Initial treatment consisted of sodium bicarbonate, lipid emulsion, diazepam and norepinephrine. Because of persistent cardiogenic shock veno-arterial extracorporeal membrane oxygenation (V-A ECMO) was successfully used as a bridge to recovery. This case underscores the possible side effects of HCQ and the importance of considering ECMO in cardiogenic shock caused by HCQ intoxication which may occur also in patients with coronavirus disease 2019 (COVID-19) based on the currently frequent use of such a compound.